Sepsis-related mortality in the Czech Republic: multiple causes of death analysis - Pechholdová, M (Epidemiologie, mikrobiologie, imunologie, 2017)
AIM: Sepsis represents an increasingly frequent complication in the survival of the hospitalized persons. The nation-wide burden of the sepsis-related mortality in the Czech Republic has not yet been analysed. The present study aims to assess the trends and the disparities in the sepsis-related mortality in the Czech Republic for the period 1998-2011 using multiple causes of death reported on the death certificates. MATERIALS AND METHODS: Individual death records provided by the Institute for Health Information and Statistics were used to identify sepsis-related deaths based on the codes of the 10th revision of the International classification of the diseases (ICD-10). Frequencies, age-standardized rates and comorbidity patterns were studied. RESULTS: A total of 41,425 cases (3%) out of 1,456,539 deaths within the period 1998-2011 were associated with sepsis. In 2011, sepsis was reported in 8% of all in-hospital deaths. Sepsis is the most likely to be reported as immediate cause of death (66%), which results in its considerable underestimation in the underlying cause of death statistics. The sepsis-related mortality almost tripled between 1998 and 2011, and the most of the increase is attributable to persons aged 65 and over. In 44% of cases, circulatory disease or cancer was reported as the underlying cause of death. Significant associations with sepsis were however found for infectious diseases, diseases of skin, and metabolic or musculoskeletal disorders. CONCLUSION: Multiple cause of death analysis of sepsis-related mortality revealed that sepsis represents a growing burden related to the population ageing and increased prevalence of complications of chronic diseases. The observed upward trends, as well as the expected continuation of the ageing process, may result in further increase of sepsis-related mortality. Preventive measures in the clinical management of sepsis are recommended.
Keywords: Communicable Diseases; Česká republika; sepse; Sepsis; komorbidita; lidé; senioři; Comorbidity; příčina smrti; Aged; Czech Republic; sepsis - septicaemia - mortality - comorbidity - ageing.; Cause of Death; infekční nemoci; Humans